Konsep Pengembangan Masyarakat Plural Perspektif Al-Qur’an - Makmun, Fariza (BINA' AL-UMMAH, 2020)
Pluralism is understood as a concept that recognizes diversity in a variety of ways, whether religious, racial, ethnic or cultural diversity. Existing diversity actually becomes intellectual property to be studied. In terms of pluralism, Islamic religion has provided a clear concept that can be used as a guide for the people. The Koran implements fundamental principles for the reality of religious pluralism. The principle that sustains religious pluralism in the Qur'an, first, is the recognition of the existence of Religions. the Qur'an's acceptance of religions other than Islam to coexist, as contained in the words of God, QS. An-Nahl, verse: 93. Second, there is a unity of the divine message, to fear Allah as in QS. Al-Nisa '(4): 131. The message of piety is in principle addressed to all mankind. Third, the principle of freedom of belief, namely the prohibition of imposing religion as in the Qur'an, QS. Al-Baqarah (2): 256. Fourth, there is the unity of the teachings of the prophets, that the basic teachings of religion are the same (even though their outward forms differ) from the first Prophet to the last Prophet, QS. As-Shura (42): 13.